The complete mitochondrial genome of camphor lace bug, Stephanitis macaona (Hemiptera: Tingidae) and its phylogenetic analysis - Tian-Qi Tian; Feng Zhang; Ying-Yan Zhai; Ying-Mei Li; Zeng-Yi Li; Bo Hong (Mitochondrial DNA. Part B. Resources)
Stephanitis macaona Drake, 1948 (Hemiptera: Tingidae) is an important pest of camphor trees. The complete mitochondrial genome of S. macaona was sequenced and assembled in this paper. The circular genome is 15,407 bp in length and contains 37 genes (13 protein-coding genes, 22 transfer RNA genes, 2 ribosomal RNA genes) as well as one AT-rich region (GenBank accession no. PP868166). The average nucleotide composition is 44.04% for A, 34.40% for T, 12.50% for C, and 9.06% for G. The percentage of A + T contents is 78.44%. The maximum-likelihood phylogenetic analysis of the concatenated nucleotide sequences of 13 PCGs from 21 species in the family Tingidae and two outgroup species was performed. The results indicated that Stephanitis macaona does not form sister relationships with any other species, instead nesting within the genus Stephantis. This study provides significant molecular data for advancing the evolutionary and phylogeographic analysis of S. macaona.